2016
DOI: 10.1007/s10620-016-4120-7
|View full text |Cite
|
Sign up to set email alerts
|

APOC3 rs2070666 Is Associated with the Hepatic Steatosis Independently of PNPLA3 rs738409 in Chinese Han Patients with Nonalcoholic Fatty Liver Diseases

Abstract: The APOC3 rs2070666 A allele is a risk factor for NAFLD independent of obesity, dyslipidemia, and PNPLA3 rs738409, and it might contribute to increased liver fat content in Chinese Han population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Zhou et al [14] have reported an association between polymorphisms on hepatic lipase and liver damage too. The APOC3 rs2070666 A allele is a risk factor for NAFLD independent of obesity, dyslipidemia, and PNPLA3 rs738409, and it might contribute to increased liver fat content [30]. Lipid metabolism is the cornerstone in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [14] have reported an association between polymorphisms on hepatic lipase and liver damage too. The APOC3 rs2070666 A allele is a risk factor for NAFLD independent of obesity, dyslipidemia, and PNPLA3 rs738409, and it might contribute to increased liver fat content [30]. Lipid metabolism is the cornerstone in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…PNPLA3 I148M and TM6SF2 E167K variations are closely related to the prevalence and severity of NAFLD. This group of NAFLD patients may not have characteristics of IR and MetS . Other independent risk factors for the occurrence and development of NAFLD include hyeruricemia, hyperhemoglobinemia, hypothyroidism, hypopituitarism, sleep apnea syndrome and polycystic ovary syndrome …”
Section: Epidemiology and Screeningmentioning
confidence: 99%
“…Apo-CIII null mice fail to stimulate VLDL production upon HFD feeding, while Apo-CIII overexpressing mice show enhanced diet-induced triglyceride accumulation in the liver [ 129 ]. A genetic variant of Apo-CIII leads to enhanced circulating Apo-CIII in humans and is associated with NAFLD [ 130 ]. Hepatic Apo-CIII expression is suppressed by RARα via a pathway involving SHP and HNF4α, thereby reducing hepatic and plasma triglyceride levels [ 131 ].…”
Section: Vitamin a And Hepatic Lipid Metabolismmentioning
confidence: 99%